Analisis Faktor-faktor yang Mempengaruhi Tingkat Literasi Keuangan UMKM Batik Tulis Lasem di Kabupaten Rembang - Wulan Suryandani; Muhammad Tahwin (BBM (Buletin Bisnis & Manajemen), 2020)
In the development of the world’s economy, business or entrepreneurial efforts are required to be able to make appropriate and effective decision making, especially in the financial sector. This research was conducted to analyze the factors that influence financial literacy in UMKM Batik Tulis Lasem in Rembang Regency. The variables used in this study are education level, gender, and income level. This has implications for good finance that will help MSMEs to take effective financial decisions for the sustainability of their businesses. This study uses binary logistic analysis to find the effect between variables with the level of financial literacy. The results of the study showed that none of the variables used in the study had a significant influence on the level of financial literacy at UMKM Batik Tulis Lasem.